Cholelithiasis risk factors in young age patients less than 30 years of age - Khan, Ameer; Ahmed, Mohammad Kashif; Faraz, Neda; Husain, Mehmood (International Journal of Research in Medical Sciences, 2026)
Background: Gall-stone disease is increasingly reported in adults younger than 30 years, yet age-specific determinants remain underexplored in South Asia. The objective was to identify independent risk factors for symptomatic cholelithiasis in North-Indian adults aged 15–29 years and to develop a pragmatic bedside risk-score. Methods: A prospective, unmatched case–control study enrolled 50 ultrasound-confirmed gall-stone cases and 50 stone-free controls at a tertiary hospital between January and June 2024. Exposures included anthropometry, dietary glycaemic load, physical activity, hormonal factors, family history and β-thalassaemia trait. Multivariable logistic regression generated adjusted odds ratios (aOR), and a four-item risk-score was evaluated by receiver-operating-characteristic analysis. Results: Central obesity (waist-to-height ≥0.50) was present in 70% of cases versus 40% of controls (aOR 3.0; 95% CI 1.3–6.9). A high-glycaemic diet was reported by 60% versus 32% (aOR 2.6; 1.1–6.1). Among females, prolonged combined oral-contraceptive use ≥60 months occurred in 42% versus 12% (aOR 4.1; 1.1–15.6). Family history showed a crude OR 3.2 but attenuated after adjustment (aOR 2.4; 0.8–7.4). β-thalassaemia trait (12% versus 4%) preferentially yielded pigment stones yet was not an independent predictor (aOR 3.4; 0.6–19.0). The four-item score (central obesity, high-glycaemic diet, inactivity, family history) achieved an AUROC of 0.82, with a cut-off ≥2 giving 80% sensitivity and 70% specificity. Conclusion: Early-onset cholelithiasis in this cohort is chiefly a metabolic–hormonal entity linked to visceral adiposity, refined-carbohydrate intake and extended oestrogen exposure. Simple anthropometric and lifestyle measures can triage high-risk youth for targeted counselling and ultrasound surveillance, offering a scalable strategy to curb the rising burden of gall-stone disease in the most productive years of life.